PELATIHAN MEDIA PEMBELAJARAN IPA INOVATIF UNTUK GURU SEKOLAH DASAR DI KABUPATEN TAPANULI TENGAH - Dongoran, Jhonas; Sinaga , Eka Margareta; Zai, Setiani; Turnip, Rotama Angelina; Simbolon , Indah; Nababan , Evi Lasrohana (ASOSIASI IDEBAHASA KEPRI, 2025)
Science learning requires a contextual and creative approach that enables students to actively engage in understanding scientific concepts. One of the key strategies to achieve meaningful learning is through the use of innovative instructional media. This community service activity aimed to improve the capacity of elementary science teachers in Central Tapanuli Regency in designing and utilizing relevant and effective instructional media. The activity was carried out through interactive lectures, hands-on practice, as well as discussion and simulation sessions on media implementation. The results showed that teachers experienced improvements in conceptual understanding, technical skills, and their enthusiasm for innovation. Teachers successfully created various instructional media such as educational games, simple models made from recycled materials, and digital media using interactive PowerPoint. This activity had a positive impact on strengthening teachers' professional competencies and fostering a collaborative culture, along with increased awareness of the importance of publishing innovative educational products. The recommendation from this activity is the need for continuous mentoring and replication of the program in other regions to expand the benefits of systematic teacher capacity development.